Taxonomy, Ecology and Distribution of Juniperus oxycedrus L. Group in the Mediterranean Basin Using Bioclimatic, Phytochemical and Morphometric Approaches, with Special Reference to the Iberian Peninsula - Ana Cano Ortiz (Forests, 2021)
Several studies have been conducted in the past to clarify various aspects of species in the genus Juniperus L. One critical group is Juniperus oxycedrus L., especially from the taxonomical point of view. For this reason, we have studied the ecology, taxonomy and distribution of the taxa in the J. oxycedrus group. From an ecological and distribution standpoint, in this work we use the ombroedaphoxeric index (Ioex) to explain the presence of Juniperus populations in ombrotypes that are not optimum for these taxa. The controversy over the taxonomy of J. oxycedrus subsp. badia (H. Gay) Debeaux and J. oxycedrus subsp. lagunae (Pau ex C. Vicioso) Rivas Mart. is clarified, and it is accepted as a valid name, J. oxycedrus subsp. badia. The phytochemical differences in essential oils (EO) are addressed and their similarities analyzed; greater similarities are observed between oxycedrus and badia, and between navicularis Gand. and macrocarpa (Sm.) Ball. species. The phytochemical, molecular and distribution differences allow J. oxycedrus subsp. macrocarpa (Sm.) Ball and J. navicularis Gand. to be maintained as species. The results obtained make it possible to establish the rank to which the taxa belong and allow clear discrimination between species in groups that are difficult to interpret. Ecological, bioclimatic, phytochemical and morphometric similarities allow us to subordinate the subsp. macrocarpa to the species J. navicularis.